THE USE OF GRAPHICS DURING THE PSYCHOMOTOR EVALUATION N PHYSIOTHERAPY - Talon Bermejo, A; Paz Lourido, B (Cuestiones de Fisioterapia, 2003)
One of the main professional functions of physical therapists is to make evaluation proofs before, during and after physical therapy interventions. In this article we present a graph to make this evaluation an easier process because it allows us to get information about the regular development of babies and at the same time, to note the psychometrical changes we found in the examination.